1993
DOI: 10.1002/lsm.1900130118
|View full text |Cite
|
Sign up to set email alerts
|

Rationale for automatic scanners in laser treatment of port wine stains

Abstract: Laser therapy of port wine stains (PWS) is well established. However, the application of lasers to PWS treatment over the last decade has resulted in the use of many laser systems. The goal of this study is to describe the different laser parameters, treatment techniques, and delivery systems. Two methods, coagulation and microvaporization, are used to destroy the abnormal blood vessels. The coagulation method results in excellent treatment, but it requires careful control of laser parameters during the treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1993
1993
2002
2002

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The ideal pulse duration for PWS vessels may lie between 1 and 10 ms when the vessel diameter is 30–150 μm 14 . The argon‐pumped dye laser has a much longer pulse duration that results in coagulation, with non‐selective damage of the vessel wall, dermis and epidermis clinically expressed as skin blanching 15 . This perivascular collagen damage with fibrosis might contribute to substantial diminution of vessel diameter and prevent recanalization 16 .…”
Section: Discussionmentioning
confidence: 99%
“…The ideal pulse duration for PWS vessels may lie between 1 and 10 ms when the vessel diameter is 30–150 μm 14 . The argon‐pumped dye laser has a much longer pulse duration that results in coagulation, with non‐selective damage of the vessel wall, dermis and epidermis clinically expressed as skin blanching 15 . This perivascular collagen damage with fibrosis might contribute to substantial diminution of vessel diameter and prevent recanalization 16 .…”
Section: Discussionmentioning
confidence: 99%
“…It also allows longer endurance than humans in the same task. Many experts have demonstrated that the precise control of dosimetry is an important criteria for successful laser therapy [9]. Thus, automated treatment devices will surely improve the treatment results by using lasers in an optimal fashion.…”
Section: Automated Pws Removalmentioning
confidence: 99%
“…Two categories of automated treatment devices have been developed: scanners and automated handpieces [9]. In the first category, the two systems developed are the MultiscanTM and the ScanalTM.…”
Section: Attempts At Automated Pws Removalmentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of the technique used, some of the major problems with the argon laser have been the lack of re‐producibility of the results, the fact that clinical outcome depends on the individual laser surgeon's technique, lack of homogeneous energy delivery, and the inability to treat large areas rapidly. These problems have recently been addressed with new scanners and automated hand‐pieces 10 . These instruments provide rapid, reproducible homogeneous laser treatment to large surface areas.…”
Section: Port‐wine Stainsmentioning
confidence: 99%